Preschool Teachers’ Managing Online Learning During the Covid-19 Pandemic Situation in Schools Under the Bangkok Metropolitan Administration - Pongyeewha, Supatchara; Hemchayart, Worawan (An Online Journal of Education, 2022)
This survey research aimed to analyze preschool teachers’ management online learning during the Covid-19 pandemic in schools under the Bangkok Metropolitan Administration by examining online teaching preparation, online learning activities, and online assessment. The samples consisted of 160 preschool teachers in the second semester of the 2021 academic year in schools under the Bangkok Metropolitan Administration. A questionnaire was used for data collection and then analyzed using frequency distribution, percentage, means, standard deviation, and content analysis. The research results found that the overall management of online learning for preschool teachers was at a high level (M = 4.30, SD = 0.45). Considerably, all aspects were found to be at a high level of practice (4.26 ≤ M ≤ 4.34). These aspects included (1) online teaching preparation (M = 4.26, SD = 0.48), consisting of activity plans (M = 4.28, SD = 0.52) and learning facilitation (M = 4.24, SD = 0.55); (2) online learning activities (M = 4.31, SD = 0.52), consisting of the types of learning activities (M = 4.28, SD = 0.54), interaction with learners (M = 4.35, SD = 0.66); and (3) online assessment (M = 4.34, SD = 0.52), consisting of the types of learning assessments (M = 4.37, SD = 0.53) and parental involvement in assessment (M = 4.31, SD = 0.59), respectively.